Solid-state battery

By adding Li ions, Mg and specific elements to the oxide ceramic, an outer packaging part with better moisture resistance and reactivity resistance is formed, which solves the problem of decomposition caused by reaction between solid electrolyte and oxide ceramic, and improves the safety and stability of the battery.

CN119923734APending Publication Date: 2025-05-02MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380068764.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-28
Filing Date
2023-08-14
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In existing solid batteries, when the oxide ceramics do not contain Li ions, the solid electrolyte reacts with the oxide ceramics, resulting in the decomposition of the solid electrolyte and the by-products. Especially when using garnet or LISICON type solid electrolytes with high reactivity, the decomposition is even more serious.

Method used

By adding Li ions, Mg and selected Group 4 or Group 5 elements to the oxide ceramic, an outer packaging portion with better moisture resistance and reactivity resistance is formed.

Benefits of technology

The moisture resistance and reactivity resistance of the outer packaging part are improved, the decomposition of solid electrolytes is prevented, and the safety and stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923734A_ABST
    Figure CN119923734A_ABST
Patent Text Reader

Abstract

Provided is a solid-state battery having an outer packaging part that includes an oxide ceramic that is capable of forming an outer packaging part having more sufficiently excellent moisture resistance and that has more sufficiently excellent reaction resistance with a solid electrolyte. The present invention relates to a solid-state battery having an outer packaging part (2), the outer packaging part (2) containing an oxide ceramic, the oxide ceramic containing: Li (lithium); mg (magnesium); and one or more elements (M) selected from the group consisting of Group 4 and Group 5 elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a solid battery. Background Art

[0002] In recent years, as the power source of portable electronic devices such as mobile phones and portable personal computers, the demand for batteries has been greatly expanded. In batteries used for such purposes, electrolytes (electrolytes) such as organic solvents have been used as media for moving ions. However, in the battery of the above structure, there is the danger of electrolyte leakage. In addition, the organic solvents used in the electrolyte are flammable substances. Therefore, it is required to improve the safety of the battery.

[0003] Therefore, in order to improve the safety of batteries, research on solid batteries using solid electrolytes as electrolytes instead of electrolyte solutions is being conducted.

[0004] For example, Patent Documents 1 to 4 propose solid batteries each having an outer casing made of oxide ceramic on the outer surface of a battery element including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer therebetween.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: WO2019 / 167856

[0008] Patent Document 2: Japanese Patent Application Publication No. 2007-173212

[0009] Patent Document 3: Japanese Patent Application Publication No. 2003-92092

[0010] Patent Document 4: WO2019 / 181909 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] However, the inventors of the present invention have found that the above-mentioned existing fixed batteries have the following new problems:

[0013] When the oxide ceramic contained in the outer packaging does not contain Li ions, the solid electrolyte contained in the battery element reacts with the oxide ceramic, and the solid electrolyte decomposes to generate by-products. In particular, when a highly reactive solid electrolyte having a garnet-type or LISICON-type crystal structure is used, the solid electrolyte is easily decomposed.

[0014] Therefore, it was found that the side reaction can be suppressed by making the oxide ceramic contain Li ions. However, when the outer casing is formed of the oxide ceramic containing Li ions, the moisture resistance of the outer casing itself is reduced.

[0015] An object of the present invention is to provide a solid battery having an outer casing, wherein the outer casing includes an oxide ceramic, wherein the oxide ceramic can form an outer casing having sufficiently excellent moisture resistance and has sufficiently excellent resistance to reactivity with a solid electrolyte.

[0016] Technical solutions for solving technical problems

[0017] The present invention relates to a solid battery having an outer packaging portion, wherein the outer packaging portion includes an oxide ceramic, and the oxide ceramic contains:

[0018] Li (lithium);

[0019] Mg (magnesium); and

[0020] One or more elements (M) selected from the group consisting of elements of Group 4 and Group 5.

[0021] Effects of the Invention

[0022] According to the present invention, it is possible to provide a solid battery having an outer casing having sufficiently excellent moisture resistance and containing an oxide ceramic having sufficiently excellent resistance to reactivity with a solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram showing an example of the solid battery of the present invention, and is a composite diagram of a perspective view and a cross-sectional view.

[0024] Figure 2 This is a schematic perspective view showing another example of the solid battery of the present invention.

[0025] Figure 3 The XRD measurement result data when the reactivity resistance was determined in Example 4 are shown. DETAILED DESCRIPTION

[0026] [Solid-state battery]

[0027] The present invention provides a solid battery. The "solid battery" mentioned in this specification refers to a battery whose constituent elements (especially the electrolyte layer) are composed of solids in a broad sense, and refers to an "all-solid battery" whose constituent elements (especially all constituent elements) are composed of solids in a narrow sense. In a preferred embodiment, the solid battery of the present invention is a stacked solid battery in which the layers constituting the battery structural unit are stacked on each other, and preferably, each of such layers is composed of a sintered body. The "solid battery" mentioned in this specification includes so-called "secondary batteries" that can be repeatedly charged and discharged and "primary batteries" that can only be discharged. In a preferred embodiment of the present invention, the "solid battery" is a "secondary battery". "Secondary battery" is not overly restricted to its name, for example, it can also include electrochemical devices such as "power storage equipment". The "solid electrolyte" mentioned in this specification refers to an electrolyte that does not contain gel-like and liquid-like electrolytes (liquids).

[0028] The "top view" mentioned in this specification refers to the state (top view or bottom view) when observing the object from the upper side or lower side along the thickness direction based on the stacking direction of the layers described later constituting the solid battery. In addition, the "section view" mentioned in this specification refers to the cross-sectional state (section view) when observed from a direction approximately perpendicular to the thickness direction L of the stacking direction of the layers described later constituting the solid battery. "Side view" refers to the state when the solid battery is placed and observed from the front side in the thickness (height) direction, which has the same meaning as the side view. The placement is to place the surface (plane) with the largest area of ​​the appearance of the solid battery as the bottom surface. The "up and down directions" and "left and right directions" used directly or indirectly in this specification are respectively equivalent to the up and down directions and left and right directions in the figure. Unless otherwise specified, the same figure mark or symbol represents the same part, part or the same meaning. In a preferred embodiment, it can be understood that the vertical direction downward (i.e., the direction of gravity) is equivalent to the "downward direction", and the opposite direction is equivalent to the "upward direction".

[0029] The solid battery of the present invention may have any shape in a plan view, but is generally rectangular, including square and rectangular.

[0030] The solid battery of the present invention has, for example, Figure 1 The solid battery of the present invention comprises a battery element 1 and an outer casing 2 covering the surface of the battery element 1, and generally comprises an external electrode 3 for extracting the power (especially current) generated by the battery element to the outside. Figure 1 This is a schematic cross-sectional view showing an example of the solid battery of the present invention.

[0031] (External Packaging Department)

[0032] The outer packaging part 2 is a component covering the outside of the battery element 1, and has the function of covering the battery element 1 and preventing moisture from invading the battery element 1. The outer packaging part 2 usually has not only such a function, but also has the function of protecting the battery element electrically, physically and chemically, so it can also be called a protective layer or protective film. The outer packaging part 2 includes a main surface outer packaging part 2a (for example, a group of main surface outer packaging parts 2a) covering the main surface of the battery element 1 and a side outer packaging part 2b (for example, a group of side outer packaging parts 2b) covering the side of the battery element 1. The outer packaging part 2 usually has a layer form or a film form. The outer packaging part 2 can be in direct contact with the surface (especially the main surface and / or the side) of the battery element 1, or it can be in indirect contact via other layers (or films). From the viewpoint of more fully exerting the effect of the present invention, it is preferred that the outer packaging part 2 is in direct contact with the surface (especially the main surface and / or the side) of the battery element 1.

[0033] In the solid battery of the present invention, the outer packaging part 2 contains a specific oxide ceramic. In the present invention, at least one of the main surface outer packaging part and the side outer packaging part contains a specific oxide ceramic. From the viewpoint of further improving moisture resistance and reactivity resistance, it is preferred that both the main surface outer packaging part and the side outer packaging part contain a specific oxide ceramic.

[0034] In this specification, moisture resistance refers to a property of preventing moisture from entering, and in particular, may refer to a property of being less susceptible to moisture even under high temperature and high humidity conditions (for example, a property of being less susceptible to moisture absorption).

[0035] Reaction resistance refers to the property that the outer packaging part (especially the oxide ceramic contained in the outer packaging part) is difficult to react (such as a side reaction) even if it is fired (for example, at 800° C. for 5 hours) with the solid electrolyte contained in the battery element. Reaction resistance can also be a property that the oxide ceramic and the solid electrolyte are difficult to react with each other even if they are fired together.

[0036] In the present invention, the oxide ceramic contained in the outer packaging portion contains: Li (lithium); Mg (magnesium); and one or more elements (M) selected from the group consisting of elements of Group 4 and Group 5. In detail, element M is one or more elements selected from the group consisting of Ti (titanium), Zr (zirconium), Hf (hafnium), Ta (tantalum), and Nb (niobium). From the viewpoint of further improving moisture resistance, element M preferably includes Ti, more preferably only includes Ti, or includes Ti and Zr or Ta. In the present invention, the oxide ceramic can obtain an outer packaging portion with excellent moisture resistance and reactivity resistance by combining Li, Mg and element M. When the oxide ceramic does not contain Li, does not contain Mg, and does not contain element M, at least one of the characteristics of moisture resistance or reactivity resistance is reduced.

[0037] In the oxide ceramic, the molar ratios Li / M and Mg / M are not particularly limited, but are preferably within the following ranges from the viewpoint of further improving moisture resistance and reactivity resistance.

[0038] ·Li / M

[0039] Preferably, 0<Li / M≤5;

[0040] More preferably, 0.8≤Li / M≤4.2;

[0041] More preferably, 0.8≤Li / M≤2.1.

[0042] Mg / M

[0043] Preferably, 0.1≤Mg / M≤9.8;

[0044] More preferably, 0.3≤Mg / M≤9.8;

[0045] More preferably, 0.8≤Mg / M≤4.2.

[0046] As Li / M and Mg / M in the oxide ceramic, values ​​calculated from the contents (or molar ratios) of Li, Mg, and M measured by the same method as the method for analyzing the chemical composition of the oxide ceramic described later are used.

[0047] The oxide ceramic may have any chemical composition as long as it has the above-mentioned molar ratio. From the viewpoint of further improving moisture resistance and reactivity resistance, the oxide ceramic preferably has a chemical composition represented by the following general formula (1).

[0048] Li α1 A α2 Mg β M γ O δ (1) In formula (1), A is one or more elements selected from the group consisting of Na, K, Rb, Ca, Sr, Ba, Sc, Y, Mo, W, Zn, Al, Ga, Ge, Sn, Sb, and Bi.

[0049] M is one or more elements selected from the same group as the above-mentioned element M. From the viewpoint of further improving moisture resistance, it preferably includes one or more elements selected from the group consisting of Ti, Zr, Hf, Nb and Ta, more preferably includes Ti, further preferably includes only Ti, or includes Ti, Zr or Ta.

[0050] In formula (1), α1 / γ and β / γ correspond to the molar ratios Li / M and Mg / M, respectively. Therefore, α1 / γ satisfies the same range as the molar ratio Li / M, and from the viewpoint of further improving moisture resistance and reactivity resistance, preferably satisfies the preferred range of Li / M, more preferably satisfies the more preferred range of Li / M, and further preferably satisfies the further preferred range of Li / M. β / γ satisfies the same range as the molar ratio Mg / M, and from the viewpoint of further improving moisture resistance and reactivity resistance, preferably satisfies the preferred range of Mg / M, more preferably satisfies the more preferred range of Mg / M, and further preferably satisfies the further preferred range of Mg / M.

[0051] δ={α1+aα2+2β+nγ} / 2

[0052] (n is the average price of M and M', a is the average price of A)

[0053] Specifically, n is the average value of M and M'. The average value of M and M' is used as B 1 For example, when it is confirmed that the number of X with a valence of a+ is n1, the number of Y with a valence of b+ is n2, and the number of Z with a valence of c+ is n3, it is the same as the above A 1 The average price is the same value.

[0054] a is the average valence of A. The average valence of A, for example, when it is confirmed that there are n1 elements X with a valence of a+, n2 elements Y with a valence of b+, and n3 elements Z with a valence of c+, is a value represented by (n1×a+n2×b+n3×c) / (n1+n2+n3).

[0055] It should be noted that the oxygen number δ may deviate from the above value by about ±10%. That is, some oxygen vacancies or interstitial oxygen may be contained.

[0056] In the formula (1), α1 generally satisfies 0<α1<1.0, and preferably satisfies 0.15<α1<0.70, and more preferably satisfies 0.29≤α1≤0.50, from the viewpoint of further improving moisture resistance and reactivity resistance.

[0057] α2 usually satisfies 0≤α2≤1.0, and preferably satisfies 0≤α2≤0.5, and more preferably is 0, from the viewpoint of further improving moisture resistance and reactivity resistance.

[0058] β usually satisfies 0<β<1.0, and preferably satisfies 0.03≤β<0.85, and more preferably satisfies 0.25≤β≤0.60, from the viewpoint of further improving moisture resistance and reactivity resistance.

[0059] γ usually satisfies 0<γ<1.0, and preferably satisfies 0.05<γ<0.35, and more preferably satisfies 0.14≤γ≤0.26 from the viewpoint of further improving moisture resistance and reactivity resistance.

[0060] The chemical composition of the oxide ceramic can be obtained by performing ICP analysis (inductively coupled plasma analysis), LA-ICP-MS (laser ablation ICP mass spectrometry) analysis, etc. EDX (energy dispersive X-ray spectroscopy) and WDX (wavelength dispersive X-ray spectroscopy) can also be used. In addition, the chemical composition can also be obtained by performing quantitative analysis (composition analysis) on any 100 points of each of any 100 sintered particles and calculating their average value.

[0061] The crystalline structure of the oxide ceramic is not particularly limited, and for example, it may have a rock salt type crystalline structure, a spinel type crystalline structure, a layered rock salt type crystalline structure, or a mixed structure thereof. From the viewpoint of further improving moisture resistance and reactivity resistance, the oxide ceramic preferably has a rock salt type crystalline structure and / or a spinel type crystalline structure (particularly a rock salt type crystalline structure or a mixed structure of a rock salt type crystalline structure and a spinel type crystalline structure), and more preferably has a rock salt type crystalline structure.

[0062] The fact that an oxide ceramic has a rock salt type crystal structure means that the oxide ceramic not only has a "rock salt type crystal structure", but also includes the meaning of having a "crystal structure similar to a rock salt type". In detail, the oxide ceramic has a crystal structure that can be identified as a rock salt type or a crystal structure similar to a rock salt type by a person skilled in the art in the field of solid batteries in X-ray diffraction. In more detail, the oxide ceramic can show a diffraction pattern of a so-called rock salt type crystal structure at a specified incident angle in X-ray diffraction: one or more main peaks corresponding to the Miller index inherent in ICDD Card No. 00-004-0829, or as a crystal structure similar to a rock salt type, one or more main peaks corresponding to the Miller index inherent in the so-called rock salt type crystal structure refer to one or more main peaks that can show different incident angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensities or diffraction intensity ratios) due to differences in composition. As a representative diffraction pattern of a crystal structure similar to a rock salt type, for example, ICDD Card No. 00-036-0308 can be cited.

[0063] The oxide ceramic having a spinel-type crystal structure means that the oxide ceramic not only has a "spinel-type crystal structure", but also includes the meaning of having a "spinel-type crystal structure". In detail, the oxide ceramic has a crystal structure that can be identified as a spinel-type or spinel-type-like crystal structure by a person skilled in the art in the field of solid batteries in X-ray diffraction. In more detail, the oxide ceramic can show one or more main peaks corresponding to the Miller index inherent in the so-called spinel-type crystal structure diffraction pattern: ICDD Card No.01-072-6998 at a specified incident angle in X-ray diffraction, or as a spinel-type-similar crystal structure, one or more main peaks corresponding to the Miller index inherent in the so-called spinel-type crystal structure means that one or more main peaks with different incident angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensities or diffraction intensity ratios) due to differences in composition can be shown.

[0064] The fact that the oxide ceramic has a mixed phase structure of a rock salt type crystal structure and a spinel type crystal structure means that the oxide ceramic contains an oxide ceramic having both the rock salt type crystal structure and the spinel type crystal structure.

[0065] The oxide ceramic having a layered rock salt type crystal structure means that the oxide ceramic not only has a "layered rock salt type crystal structure", but also includes the meaning of having a "crystal structure similar to the layered rock salt type". In detail, the oxide ceramic has a crystal structure that can be identified as a layered rock salt type or a crystal structure similar to the layered rock salt type by a person skilled in the art in the field of solid batteries in X-ray diffraction. In more detail, the oxide ceramic can show one or more main peaks corresponding to the Miller index inherent in the so-called layered rock salt type crystal structure diffraction pattern: ICDD Card No.00-033-0831 at a specified incident angle in X-ray diffraction, or as a crystal structure similar to the layered rock salt type, one or more main peaks corresponding to the Miller index inherent in the so-called layered rock salt type crystal structure means that one or more main peaks can be shown with different incident angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensities or diffraction intensity ratios) due to differences in composition. Representative diffraction patterns of a crystal structure similar to the layered rock salt type include, for example, ICDD Card No. 00-033-0843.

[0066] Oxide ceramics can be manufactured by all methods as long as the oxide ceramics of the desired composition can be obtained. For example, oxide ceramics can be obtained by weighing raw materials containing Li source, Mg source and element M source to make it into the desired composition, and then sintering after fully mixing with water. The sintering temperature is not particularly limited, for example, it can be above 800°C and below 1200°C (especially above 850°C and below 1100°C). The sintering time is not particularly limited, for example, it can be above 1 hour and below 10 hours (especially above 3 hours and below 7 hours). As a Li source, for example, lithium carbonate (Li2CO3) can be used. As a Mg source, for example, magnesium oxide (MgO) can be used. As an element M source, for example, titanium oxide (TiO2), niobium oxide (Nb2O5), zirconium oxide (ZrO2), tantalum oxide (Ta2O5), and hafnium oxide (HfO2) can be used. In the manufacture of oxide ceramics, the addition ratio of the Li source, Mg source and element M source when added directly becomes the final composition of the obtained oxide ceramic. Therefore, by adjusting the charging ratio of the Li source, the Mg source, and the element M source, the above-mentioned molar ratios Li / M and Mg / M can be controlled.

[0067] In the present invention, the outer packaging part 2 may also contain other oxide ceramics in addition to the above-mentioned specific oxide ceramics. As other oxide ceramics, oxides containing Bi can be listed. For example, Li-Bi-O series oxides, Li-Mg-Bi-O series oxides, Bi2O3, Mg-Bi-O series oxides, etc. can be listed. The content of the above-mentioned specific oxide ceramics in the outer packaging part 2 can usually be an area ratio of more than 60% and less than 100%, especially an area ratio of more than 90% and less than 100%. The area ratio can be measured as follows. First, the solid battery is broken so that the fracture surface of the ceramic of the outer packaging part is exposed. The fracture surface is ground using a cross-section polisher to obtain a ground surface. In the area of ​​the outer packaging part of the ground surface, EDX analysis is performed on any surface, and the area where Mg, element M, element A are detected, and Li is detected by TOF-SIMS is regarded as the area of ​​the above-mentioned specific oxide ceramic. Thus, it can be measured by calculating the area ratio of the oxide ceramic relative to the area of ​​the outer packaging part.

[0068] The thickness of the outer packaging part 2 is usually preferably 1 μm to 500 μm, more preferably 5 μm to 100 μm, and further preferably 5 μm to 50 μm. The thickness of the outer packaging part 2 is the average thickness of 100 arbitrary locations.

[0069] The relative density of the outer packaging part 2 is usually 90% or more and 100% or less, and preferably 95% or more and 100% or less. The relative density of the outer packaging part can also be measured using the Archimedean method.

[0070] The outer casing 2 is generally insulating. Insulation means that the outer casing 2 has neither ion conductivity nor electron conductivity. For example, the ion conductivity of the outer casing 2 is generally 1×10 -7 S / cm or less, especially ion conductivity of 1×10 -10 S / cm or less. The ionic conductivity of the outer packaging part 2 is usually 1×10 -18 S / cm or more. For example, the electron conductivity of the outer packaging part 2 is usually 1×10 -7 S / cm or less, especially 1×10 -10 S / cm or less. The electron conductivity of the outer packaging part 2 is usually 1×10 -18 S / cm or more.

[0071] The oxygen permeability in the thickness direction of the outer packaging portion 2 may be, for example, 10 -1 cc / m 2 / day / below air pressure, especially 10 -3 cc / m 2 / day / below air pressure.

[0072] The H2O permeability in the thickness direction of the outer packaging part 2 can be, for example, 10 -2 g / m 2 / day or less, especially 10 -4 g / m 2 / day or less. The H2O permeability is measured at 25°C by the cup method, carrier gas method, pressure method, and Ca corrosion method.

[0073] The main surface outer packaging part 2a and the side outer packaging part 2b are Figure 1 have different forms (or different component structures) as mutually different components, but Figure 2 As shown, the main surface outer packaging portion 2a and the side outer packaging portion 2b may be integrated (or have an integrated structure). Figure 2 This is a schematic perspective view showing another example of the solid battery of the present invention. Figure 2 The solid battery has a main surface outer packaging portion 2a and a side outer packaging portion 2b integrated in a form, and Figure 1 The solid state battery is the same. Figure 2In the solid battery, not only the main surface outer packaging part 2a, but also the side outer packaging part 2b can be manufactured using the method (green sheet method) described later of pasting sheets. In particular, by manufacturing a solid battery (especially the outer packaging part 2) using a sheet corresponding to the main surface outer packaging part 2a and a sheet corresponding to the side outer packaging part 2b, the manufacture of the solid battery (especially the outer packaging part 2) becomes significantly simpler. In this case, the oxide ceramic contained in the main surface outer packaging part 2a usually has the same chemical composition as the oxide ceramic contained in the side outer packaging part 2b.

[0074] The outer packaging part 2 is preferably in direct contact with the surface (especially the main surface and / or the side surface) of the battery element 1, so that the surface and the sintered body are sintered integrally with each other. That is, the outer packaging part 2 is preferably an integral sintered body with the sintered body of the surface (especially the main surface and / or the side surface) of the battery element 1. The outer packaging part 2 and the surface of the battery element 1 form an integral sintering of the sintered bodies with each other, which means that the outer packaging part 2 and the battery element 1 are joined by sintering. In detail, the outer packaging part 2 and the battery element 1 are both sintered bodies and are sintered integrally at the same time. It should be noted that it is not necessary to strictly integrate the outer packaging part 2 and the battery element 1 in its entirety, and it is also possible not to integrate a part. The outer packaging part 2 and the battery element 1 can be integrated as a whole.

[0075] (Battery Components)

[0076] The battery element 1 is the main body of a solid battery covered by an outer packaging portion 2, and has one or more battery structural units. The battery structural unit refers to the smallest structural unit that can perform the battery function, including a group of electrode layers 1a (specifically, a positive electrode layer and a negative electrode layer facing each other) and a solid electrolyte layer 1b arranged between the group of electrode layers 1a (i.e., between the positive electrode layer and the negative electrode layer). The battery element 1 can have a single battery structure having only one battery structural unit, or it can also have a multi-battery structure in which two or more battery structural units are stacked along the stacking direction of each layer constituting each battery structural unit. The electrode layer includes a positive electrode layer and a negative electrode layer. The battery element 1 usually has an insulating portion 1c for ensuring non-electrical contact between one electrode layer and an external electrode for drawing current from another electrode layer to the outside. For example, the battery element 1 has an insulating portion 1c for ensuring non-electrical contact between the positive electrode layer and an external electrode (i.e., an external negative electrode) for drawing current from the negative electrode layer to the outside. For example, the battery element 1 has an insulating portion 1c for ensuring that the negative electrode layer is not in electrical contact with an external electrode (ie, an external negative electrode) for drawing current from the positive electrode layer to the outside. Figure 1 As shown, the battery element generally has a solid electrolyte layer 1 b at the uppermost layer and the lowermost layer of the battery element.

[0077] The battery element usually contains a solid electrolyte (hereinafter sometimes referred to as the first solid electrolyte). The first solid electrolyte contained in the battery element may have any crystalline structure, for example, it may have a garnet-type crystalline structure, a LISICON-type crystalline structure, a perovskite-type crystalline structure or a mixed-phase structure thereof. From the viewpoint of further improving moisture resistance and reactivity resistance, the first solid electrolyte contained in the battery element preferably has a garnet-type crystalline structure, a LISICON-type crystalline structure or a mixed-phase structure thereof, and more preferably has a garnet-type crystalline structure. This is because the reactivity with the oxide ceramic of the outer packaging portion becomes higher in the order of a solid electrolyte having a perovskite-type crystalline structure, a solid electrolyte having a LISICON-type crystalline structure, and a solid electrolyte having a garnet-type crystalline structure, but even if the battery element contains such a solid electrolyte, the oxide ceramic of the outer packaging portion can more fully suppress the reaction with the solid electrolyte.

[0078] When the battery element contains such a first solid electrolyte, the first solid electrolyte may include one or more layers selected from the positive electrode layer, the negative electrode layer and the solid electrolyte layer. From the viewpoint of further improving moisture resistance and reactivity resistance, such a first solid electrolyte is preferably included in at least the solid electrolyte layer.

[0079] The solid electrolyte having a garnet-type crystal structure means that the solid electrolyte not only has a "garnet-type crystal structure", but also includes the meaning of having a "garnet-type crystal structure". In detail, the solid electrolyte has a crystal structure that can be identified as a garnet-type or a garnet-type crystal structure similar to that of a person skilled in the art in the field of solid batteries in X-ray diffraction. In more detail, the solid electrolyte can show a so-called garnet-type crystal structure diffraction pattern at a specified incident angle in X-ray diffraction: one or more main peaks corresponding to the Miller index inherent in ICDD Card No. 422259, or as a garnet-type crystal structure similar to that of the so-called garnet-type crystal structure, one or more main peaks corresponding to the Miller index inherent in the so-called garnet-type crystal structure refer to, which can show one or more main peaks with different incident angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensity or diffraction intensity ratios) due to differences in composition. As a representative diffraction pattern similar to a garnet-type crystal structure, for example, ICDDCard No. 00-045-0109 can be cited.

[0080] The solid electrolyte having a garnet-type crystal structure may have any chemical composition. For example, the garnet-type solid electrolyte has a chemical composition represented by the following general formula (2).

[0081] (Li p A 1y )(La β-z B 1 z )(D 1 γ-x Bi x ) 12-δ (2)

[0082] In formula (2), A 1 Refers to the metal element occupying the Li site in the garnet crystal structure. 1 Generally, it is one or more elements selected from the group consisting of Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc) and Sc (scandium). From the viewpoint of further improving moisture resistance and reactivity resistance, A 1 Preferably, it is one or more elements selected from the group consisting of Ga (gallium) and Al (aluminum), and more preferably, it is both Ga and Al.

[0083] In formula (2), B 1 Refers to the metal element occupying the La site in the garnet crystal structure. 1 Typically, it is one or more elements selected from the group consisting of Ca (calcium), Sr (strontium), Ba (barium) and lanthanide elements. Examples of lanthanide elements include Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), and Lu (lutetium).

[0084] In formula (2), D 1 It refers to a metal element that occupies a 6-coordinated site in a garnet-type crystal structure. An example of a 6-coordinated site in a garnet-type crystal structure is Li5La3Nb2O 12 (ICDD Card No.00-045-0109) in which Nb occupies the site, Li7La3Zr2O 12 (ICDD Card. No01-078-6708) is the site occupied by Zr. 1 D represents one or more elements selected from the group consisting of transition elements capable of forming hexavalent coordination with oxygen and typical elements belonging to Groups 12 to 15. Examples of transition elements capable of forming hexavalent coordination with oxygen include Sc (scandium), Zr (zirconium), Ti (titanium), Ta (tantalum), Nb (niobium), Hf (hafnium), Mo (molybdenum), W (tungsten), and Te (tellurium). Examples of typical elements belonging to Groups 12 to 15 include In (indium), Ge (germanium), Sn (tin), Pb (lead), Sb (antimony), and Bi (bismuth). 1Usually, it is one or more elements selected from the group consisting of Zr (zirconium), Sn (tin), Sb (antimony), Ti (titanium), Ta (tantalum), Nb (niobium), Hf (hafnium), Mo (molybdenum), W (tungsten) and Te (tellurium). From the viewpoint of further improving moisture resistance and reactivity resistance, it is preferably included one or more elements selected from the group consisting of Zr (zirconium), Ta (tantalum) and Nb (niobium), and more preferably includes Zr (zirconium).

[0085] In formula (2), x satisfies 0≤x≤1.00, and preferably satisfies 0≤x≤0.70, more preferably satisfies 0≤x≤0.40, further preferably satisfies 0≤x≤0.40, and particularly preferably satisfies 0≤x≤0.20 from the viewpoint of further improving moisture resistance and reactivity resistance.

[0086] y satisfies 0≤y≤0.50. From the viewpoint of further improving moisture resistance and reactivity resistance, y preferably satisfies 0≤y≤0.40, more preferably satisfies 0≤y≤0.30, and even more preferably satisfies 0≤y≤0.20.

[0087] β satisfies 2.5≤β≤3.5. From the viewpoint of further improving moisture resistance and reactivity resistance, β is preferably 2.7≤β≤3.3, more preferably 2.8≤β≤3.2, and still more preferably 2.9≤β≤3.1.

[0088] z satisfies 0≤z≤2.00, and is preferably 0≤z≤1.00, more preferably 0≤z≤0.50, and even more preferably 0, from the viewpoint of further improving moisture resistance and reactivity resistance.

[0089] γ satisfies 1.5≤γ≤2.5. From the viewpoint of further improving moisture resistance and reactivity resistance, γ is preferably 1.7≤γ≤2.3, more preferably 1.8≤γ≤2.2, and even more preferably 1.9≤γ≤2.0.

[0090] In the formula (2), p generally satisfies 6.0≤p≤7.0, and preferably satisfies 6.0≤p≤6.6, and more preferably satisfies 6.25≤p≤6.55, from the viewpoint of further improving moisture resistance and reactivity resistance.

[0091] a is A 1 The average price of A 1 The average price of A 1 For example, when it is confirmed that there are n1 elements X with a valence of a+, n2 elements Y with a valence of b+, and n3 elements Z with a valence of c+, the value is represented by (n1×a+n2×b+n3×c) / (n1+n2+n3).

[0092] b is B 1 The average price of B1 The average price of B 1 For example, when it is confirmed that the number of X with a valence of a+ is n1, the number of Y with a valence of b+ is n2, and the number of Z with a valence of c+ is n3, it is the same as the above A 1 The average price is the same value.

[0093] c is D 1 The average price of D 1 The average price of D 1 For example, when it is confirmed that the number of X with a valence of a+ is n1, the number of Y with a valence of b+ is n2, and the number of Z with a valence of c+ is n3, it is the same as the above A 1 The average price is the same value.

[0094] δ represents the amount of oxygen deficiency, and may be 0. δ may generally satisfy 0≤δ<1. The amount of oxygen deficiency δ cannot be quantitatively analyzed even with the latest equipment, and therefore may be considered to be 0.

[0095] It should be noted that the molar ratio of each element in the chemical composition of the solid electrolyte ceramic of the present invention is not necessarily consistent with the molar ratio of each element in formula (2), and there is a tendency for it to deviate from it depending on the analysis method. However, as long as the composition deviation is not so great as to change the characteristics, the effect of the present invention can be achieved.

[0096] In the present invention, the chemical composition of the solid electrolyte ceramic can be the composition of the entire ceramic material obtained using ICP (inductively coupled plasma method). It can also be measured and calculated using ICP-AES (inductively coupled plasma emission spectrometry) and LA-ICP-MS (laser ablation inductively coupled plasma mass spectrometry). In addition, the chemical composition can be measured and calculated using XPS analysis, or it can be obtained using TEM-EDX (energy dispersive X-ray spectroscopy) and / or WDX (wavelength dispersive X-ray spectroscopy). In addition, the chemical composition can also be obtained by performing quantitative analysis (composition analysis) on any 100 points of each of any 100 sintered particles and calculating their average value.

[0097] Specific examples of the garnet-type solid electrolyte represented by the general formula (2) include Li 6.6 Ln3Z 1.6 Ta 0.4 O 12 , Li 6.4 Ga 0.05 Al 0.15 La3Zr2O 12 , Li 6.75 Ln3Z 1.75 Nb0.25 O 12 , Li 6.53 Ln3Z 1.53 Ta 0.4 Bi 0.07 O 12 .

[0098] The LISICON type crystal structure of the solid electrolyte contains β I Structure, β II Type structure, β II ' type structure, T I Type structure, T II Type structure, γ II That is, the LISICON type solid electrolyte may also include a β I Structure, β II Type structure, β II ' type structure, T I Type structure, T II Type structure, γ II From the viewpoint of further improving moisture resistance and reactivity resistance, the LISICON structure of the solid electrolyte is preferably γ II Type structure.

[0099] Solid electrolyte has γ II The solid electrolyte has a γ II The crystalline structure of the type is broadly defined as having a structure that can be identified as γ II In a narrow sense, solid electrolytes have a γ II The type structure means that the solid electrolyte shows the same characteristics as the so-called γ II -Li3VO4 type crystal structure has one or more main peaks corresponding to the Miller index. II A compound of a solid electrolyte structure (ie, solid electrolyte) is described in, for example, the document "J. solid state chem" (AR Westet. al, J. solid state chem., 4, 20-28 (1972)). As an example thereof, ICDD Card No. 01-073-2850 can be cited.

[0100] Solid electrolyte has β I The solid electrolyte has a β I The crystalline structure of the type is broadly defined as a β-type structure that can be identified as a β-type structure by those skilled in the art in the field of solid batteries. IIn a narrow sense, solid electrolytes have a β-type crystal structure. I The type structure means that the solid electrolyte shows the same characteristics as the so-called β-type structure at a specified incident angle in X-ray diffraction. I -Li3VO4 type crystal structure has one or more main peaks corresponding to the Miller index. I Compounds of the type structure (ie, solid electrolytes) are described in, for example, the document "J. solid state chem" (AR West et al., J. solid state chem., 4, 20-28 (1972)). As an example, the XRD data (Miller index corresponding to the interplanar spacing d value) described in the following table are shown.

[0101] [Table 1]

[0102]

[0103] Solid electrolyte has β II The solid electrolyte has a β II The crystalline structure of the type is broadly defined as a β-type structure that can be identified as a β-type structure by those skilled in the art in the field of solid batteries. II In a narrow sense, solid electrolytes have a β-type crystal structure. II The type structure means that the solid electrolyte shows the same characteristics as the so-called β-type structure at a specified incident angle in X-ray diffraction. II -Li3VO4 type crystal structure has one or more main peaks corresponding to the Miller index. II A compound of the type structure (ie, a solid electrolyte) is described in, for example, the document "J. solid state chem" (AR Westet. al, J. solid state chem., 4, 20-28 (1972)), and as an example thereof, ICDD Card No. 00-024-0675 can be cited.

[0104] Solid electrolyte has β II '-type structure means that the solid electrolyte has β II ' type crystalline structure, in a broad sense, refers to a structure that can be identified as β by those skilled in the art in the field of solid batteries II In a narrow sense, solid electrolytes have a β II The 'type structure means that the solid electrolyte shows the same characteristics as the so-called β II One or more main peaks corresponding to the Miller index inherent to the crystalline structure of '-Li3VO4 type. IICompounds of 'type structure (ie, solid electrolytes) are described in the document "J. solid state chem" (AR Westet.al, J. solid state chem., 4, 20-28 (1972)). As an example, the XRD data (Miller index corresponding to the plane spacing d value) described in the following table are shown.

[0105] [Table 2]

[0106]

[0107] Solid electrolyte has T I The solid electrolyte has a T I The crystalline structure of the type, in a broad sense, refers to a structure that can be recognized as T by those skilled in the art in the field of solid batteries. I In a narrow sense, solid electrolytes have a T I The T type structure refers to the fact that the solid electrolyte shows a so-called T type structure at a specified incident angle in X-ray diffraction. I -One or more main peaks corresponding to the Miller index inherent to the Li3VO4 type crystal structure. I A compound of the type structure (ie, a solid electrolyte) is described in, for example, the document “J. solid state chem” (AR West et al., J. solid state chem., 4, 20-28 (1972)). As an example thereof, ICDD Card No. 00-024-0668 can be cited.

[0108] Solid electrolyte has T II The solid electrolyte has a T II The crystalline structure of the type, in a broad sense, refers to a structure that can be recognized as T by those skilled in the art in the field of solid batteries. II In a narrow sense, solid electrolytes have a T II The T type structure refers to the fact that the solid electrolyte shows a so-called T type structure at a specified incident angle in X-ray diffraction. II -One or more main peaks corresponding to the Miller index inherent to the Li3VO4 type crystal structure. II A compound of a type structure (ie, a solid electrolyte) is described in, for example, the document “J. solid state chem” (AR Westet. al, J. solid state chem., 4, 20-28 (1972)). As an example thereof, ICDD Card No. 00-024-0669 can be cited.

[0109] The solid electrolyte having a γ0-type structure means that the solid electrolyte has a γ0-type crystal structure, and in a broad sense, it means a crystal structure that can be identified as a γ0-type crystal structure by a person skilled in the art in the field of solid batteries. In a narrow sense, the solid electrolyte having a γ0-type structure means that the solid electrolyte shows one or more main peaks corresponding to the Miller index inherent to the so-called γ0-Li3VO4-type crystal structure at a specified angle of incidence in X-ray diffraction. Compounds having a γ0-type structure (i.e., solid electrolytes) are described, for example, in the document "J. solid state chem" (AR Westet. al, J. solid state chem., 4, 20-28 (1972)). As an example thereof, the XRD data described in the following table (Miller index corresponding to the plane spacing d value) are represented.

[0110] [Table 3]

[0111]

[0112] The solid electrolyte having a LISICON type crystal structure may have any chemical composition. For example, the LISICON type solid electrolyte has a chemical composition represented by the following general formula (3).

[0113] (Li [3-ax+(5-b)(1-y)] A x )(V y B 1-y )O4 (3)

[0114] In formula (3), A is one or more elements selected from the group consisting of Na (sodium), K (potassium), Mg (magnesium), Ca (calcium), Al (aluminum), Ga (gallium), Zn (zinc), Fe (iron), Cr (chromium) and Co (cobalt).

[0115] B is one or more elements selected from the group consisting of Zn (zinc), Al (aluminum), Ga (gallium), Si (silicon), Ge (germanium), Sn (tin), P (phosphorus), As (arsenic), Ti (titanium), Mo (molybdenum), W (tungsten), Fe (iron), Cr (chromium) and Co (cobalt). From the viewpoint of further improving moisture resistance and reactivity resistance, B is preferably one or more elements selected from the group consisting of Si (silicon) and P (phosphorus), and more preferably Si (silicon) or P (phosphorus).

[0116] x has a relationship of 0≤x≤1.0, particularly 0≤x≤0.2. From the viewpoint of further improving moisture resistance and reactivity resistance, it preferably has a relationship of 0≤x≤0.1, and more preferably 0.

[0117] y has a relationship of 0≤y≤1.0, and preferably has a relationship of 0≤y≤0.85 from the viewpoint of further improving moisture resistance and reactivity resistance.

[0118] a is the average valence of A. The average valence of A, for example, when it is confirmed that there are n1 elements X with a valence of a+, n2 elements Y with a valence of b+, and n3 elements Z with a valence of c+, is a value represented by (n1×a+n2×b+n3×c) / (n1+n2+n3).

[0119] b is the average valence of B. The average valence of B is the same value as the average valence of A described above, for example, when it is confirmed that there are n1 elements X with a valence of a+, n2 elements Y with a valence of b+, and n3 elements Z with a valence of c+ as B.

[0120] Specific examples of the LISICON type solid electrolyte represented by the general formula (3) include Li 3.2 V 0.8 Si 0.2 O4、Li 3.5 P 0.5 Si 0.5 O4.

[0121] The solid electrolyte having a perovskite-type crystal structure means that the solid electrolyte not only has a "perovskite-type crystal structure", but also includes the meaning of having a "perovskite-type crystal structure". In detail, the solid electrolyte has a crystal structure that can be identified as a perovskite-type or a crystal structure similar to a perovskite-type by a person skilled in the art in the field of solid batteries in X-ray diffraction. In more detail, the solid electrolyte can show a so-called perovskite-type crystal structure diffraction pattern at a specified incident angle in X-ray diffraction: one or more main peaks corresponding to the Miller index inherent in ICDD Card No. 00-046-0465, or as a crystal structure similar to a perovskite-type, one or more main peaks corresponding to the Miller index inherent in the so-called perovskite-type crystal structure, and can also show one or more main peaks with different incident angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensities or diffraction intensity ratios) due to differences in composition. Representative diffraction patterns of a perovskite-like crystal structure include, for example, ICDD Card No. 00-046-0466.

[0122] The solid electrolyte having a perovskite crystal structure may have any chemical composition. For example, the perovskite solid electrolyte has a chemical composition represented by the following general formula (3).

[0123] Preferably having Li 3x La2 / 3-x The average chemical composition represented by TiO3 (4).

[0124] In the formula (4), x is preferably 0.09<x<0.167, and more preferably 0.10<x<0.12.

[0125] Specific examples of the perovskite-type solid electrolyte represented by the general formula (4) include Li 0.35 La 0.55 TiO3、Li 0.5 La 0.5 TiO3.

[0126] The chemical composition of a solid electrolyte refers to the average value of the chemical composition of the solid electrolyte in the thickness direction of a layer (e.g., a solid electrolyte layer) containing the solid electrolyte. The chemical composition of the solid electrolyte can be analyzed and measured by breaking a solid battery and performing EDX-based composition analysis in a field of view that converges as a whole in the thickness direction of the layer using SEM-EDX (energy dispersive X-ray spectroscopy).

[0127] The solid electrolyte can be obtained by the same method as the above-mentioned oxide ceramic except that a raw material compound containing a predetermined metal atom is used, or can also be obtained as a commercial product.

[0128] From the viewpoint of suppressing the degradation of the battery for a longer period of time, all the layers constituting the battery element 1 may also be sintered as a whole between two adjacent layers to form a sintered body. All the layers sintered as a whole between two adjacent layers to form a sintered body means that the two adjacent layers are joined by sintering. In detail, the two adjacent layers are both sintered bodies and sintered as a whole at the same time. It should be noted that it is not necessary to strictly integrate all the layers between the two adjacent layers, and it is also possible not to integrate a part. The two adjacent layers can be integrated as a whole. For example, the positive electrode layer 1a, the solid electrolyte layer 1b and the negative electrode layer 1a may also adopt a structure sintered as a whole in a prescribed stacking order.

[0129] Positive electrode layer and negative electrode layer

[0130] The positive electrode layer is a so-called positive electrode active material layer, and may also have a positive electrode collector layer in addition. In the case where the positive electrode layer has a positive electrode collector layer, the positive electrode layer may be arranged on one side of the positive electrode collector layer, or may also be arranged on both sides. The positive electrode layer is composed of a sintered body containing positive electrode active material particles, and may also be generally composed of a sintered body containing positive electrode active material particles, electron conductive material particles, and solid electrolyte particles contained in the solid electrolyte layer. The positive electrode layer (especially the positive electrode active material layer) may contain the first solid electrolyte.

[0131] The negative electrode layer is a so-called negative electrode active material layer, and may also have a negative electrode collector layer in addition. In the case where the negative electrode layer has a negative electrode collector layer, the negative electrode layer may be arranged on one side of the negative electrode collector layer, or may be arranged on both sides. The negative electrode layer is composed of a sintered body containing negative electrode active material particles, and may also be composed of a sintered body containing negative electrode active material particles, electron conductive material particles, and solid electrolyte particles contained in the solid electrolyte layer. The negative electrode layer (especially the negative electrode active material layer) may contain the first solid electrolyte.

[0132] The positive electrode active material contained in the positive electrode layer and the negative electrode active material contained in the negative electrode layer are substances that participate in the handover of electrons in the solid battery, and the ions contained in the solid electrolyte material constituting the solid electrolyte layer move (conduct) between the positive electrode and the negative electrode to carry out the handover of electrons, thereby carrying out charge and discharge. As a dielectric ion, as long as it can be charged and discharged, it is not particularly limited, for example, lithium ions or sodium ions (especially lithium ions) can be listed. The positive electrode layer and the negative electrode layer can be layers that can be embedded and deintercalated with lithium ions. That is, the solid battery of the present invention can also be a solid secondary battery in which lithium ions move between the positive electrode and the negative electrode via a solid electrolyte layer to carry out the charge and discharge of the battery.

[0133] The positive electrode active material contained in the positive electrode layer is not particularly limited, and for example, at least one selected from the group consisting of a lithium-containing phosphate compound having a NASICON structure, a lithium-containing phosphate compound having an olivine structure, a lithium-containing layered oxide, and a lithium-containing oxide having a spinel structure can be cited. As an example of a lithium-containing phosphate compound having a NASICON structure, Li3V2(PO4)3 can be cited. As an example of a lithium-containing phosphate compound having an olivine structure, Li3Fe2(PO4)3, LiMnPO4, etc. can be cited. As an example of a lithium-containing layered oxide, LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, etc. As an example of lithium-containing oxides having a spinel structure, LiMn2O4, LiNi 0.5 Mn 1.5 O4, etc.

[0134] The negative electrode active material contained in the negative electrode layer is not particularly limited, and for example, at least one selected from the group consisting of oxides, graphite-lithium compounds, lithium alloys, lithium-containing phosphate compounds having a NASICON structure, lithium-containing phosphate compounds having an olivine structure, lithium-containing oxides having a spinel structure, β-Li3VO4 structure, and oxides having a γ-Li3VO4 structure can be listed, and the oxide contains at least one element selected from the group consisting of Ti, Si, Sn, Cr, Fe, Nb, and Mo. As an example of a lithium alloy, Li-Al can be listed. As an example of a lithium-containing phosphate compound having a NASICON structure, Li3V2(PO4)3 can be listed. As an example of a lithium-containing phosphate compound having an olivine structure, Li3Fe2(PO4)3 can be listed. As an example of a lithium-containing oxide having a spinel structure, Li4Ti5O 12 As negative electrode active materials having a β-Li3VO4 structure, Li3VO4 and the like can be cited. As oxides having a γ-Li3VO4 structure, Li 3.2 V 0.8 Si 0.2 O4, etc.

[0135] The electron conductive material contained in the positive electrode layer and the negative electrode layer is not particularly limited, and metal materials such as silver, palladium, gold, platinum, aluminum, copper, and nickel, and carbon materials can be listed. In particular, carbon is difficult to react with the positive electrode active material, the negative electrode active material, and the solid electrolyte material, and has the effect of reducing the internal resistance of the solid battery, so it is preferred.

[0136] The solid electrolyte material contained in the positive electrode layer and the negative electrode layer can be selected from, for example, the same materials as the solid electrolyte material that can be contained in the solid electrolyte layer described later.

[0137] The positive electrode layer and the negative electrode layer may each independently contain a sintering aid. The sintering aid is not particularly limited, and may be, for example, at least one selected from the group consisting of lithium oxide, sodium oxide, potassium oxide, boron oxide, silicon oxide, bismuth oxide, and phosphorus oxide.

[0138] The thickness of the positive electrode layer and the negative electrode layer is not particularly limited, and may be, for example, independently 2 μm to 50 μm, and particularly 5 μm to 30 μm.

[0139] Solid electrolyte layer

[0140] The solid electrolyte layer may contain a sintering aid. The sintering aid contained in the solid electrolyte layer may be selected from the same materials as the sintering aids that may be contained in the positive electrode layer and the negative electrode layer.

[0141] The thickness of the solid electrolyte layer is not particularly limited, and may be, for example, 1 μm or more and 15 μm or less, and particularly 1 μm or more and 5 μm or less.

[0142] (External Electrode)

[0143] The external electrode 3 is a component for extracting the power (especially current) generated by the battery element 1 to the outside. The external electrode 3 includes a positive electrode side external electrode and a negative electrode side external electrode. From the viewpoint of reducing the manufacturing cost of the solid battery by integral sintering and reducing the internal resistance of the solid battery, the external electrode 3 may also have the form of a sintered body.

[0144] When the external electrode 3 has a sintered body, it may be composed of a sintered body containing electron conductive material particles and a sintering aid, for example. The electron conductive material contained in the external electrode 3 may be selected from the same materials as the electron conductive material that can be contained in the positive electrode layer and the negative electrode layer. The sintering aid contained in the external electrode 3 may be selected from the same materials as the sintering aid that can be contained in the positive electrode layer and the negative electrode layer, for example.

[0145] [Method for manufacturing solid state battery]

[0146] The method for manufacturing a solid battery of the present invention comprises:

[0147] a step of forming an unfired laminate; and

[0148] A step of firing the unfired laminate.

[0149] (Unfired Laminated Body Forming Step)

[0150] The unfired laminate can be produced by a printing method such as a screen printing method, a green sheet method using a green sheet, an impregnation method, or a composite method thereof, but it is needless to say that the method is not limited to these methods.

[0151] For example, a solid electrolyte layer and a main surface outer packaging portion are manufactured by a green sheet method. For the obtained solid electrolyte layer sheet, an electrode layer (positive electrode layer and / or negative electrode layer) and an insulating portion are formed by a printing method. After the solid electrolyte layer sheet printed with the electrode layer and the main surface outer packaging portion sheet are stacked in a prescribed order, a side outer packaging portion is formed by an immersion method. Then, an external electrode is formed by an immersion method. As a result, an unfired laminate is formed.

[0152] (Firing process)

[0153] The unfired laminate is fired. The firing is performed by removing the organic material at, for example, 500° C. in a nitrogen atmosphere containing oxygen, and then heating at, for example, 550° C. to 1300° C. inclusive.

[0154] The present invention described above includes the following preferred embodiments.

[0155] <1> A solid battery having an outer packaging portion, wherein the outer packaging portion includes an oxide ceramic, wherein the oxide ceramic contains:

[0156] Li (lithium);

[0157] Mg (magnesium); and

[0158] One or more elements (M) selected from the group consisting of elements of Group 4 and Group 5.

[0159] <2> The solid state battery according to <1> or above,

[0160] The oxide ceramic has the following molar ratio,

[0161] 0<Li / M≤5.

[0162] <3> The solid state battery according to <1> or <2>,

[0163] The oxide ceramic has the following molar ratio,

[0164] 0.1≤Mg / M≤9.8.

[0165] <4> The solid state battery according to any one of <1> to <3>,

[0166] The oxide ceramic has the following molar ratio,

[0167] 0.8≤Li / M≤4.2.

[0168] <5> The solid state battery according to any one of <1> to <4>,

[0169] The oxide ceramic has the following molar ratio,

[0170] 0.3≤Mg / M≤9.8.

[0171] <6> The solid state battery according to any one of <1> to <5>,

[0172] The oxide ceramic has the following molar ratio,

[0173] 0.8≤Li / M≤2.1.

[0174] <7> The solid state battery according to any one of <1> to <6>,

[0175] The oxide ceramic has the following molar ratio,

[0176] 0.8≤Mg / M≤4.2.

[0177] <8> The solid state battery according to any one of <1> to <7>,

[0178] The oxide ceramic has a rock salt type crystal structure, a spinel type crystal structure, a layered rock salt type crystal structure or a mixed phase structure thereof.

[0179] <9> The solid state battery according to any one of <1> to <8>,

[0180] The oxide ceramic has a rock salt type crystal structure.

[0181] <10> The solid state battery according to any one of <1> to <9>,

[0182] The element (M) is at least one selected from the group consisting of Ti, Zr, Hf, Ta and Nb.

[0183] <11> The solid state battery according to any one of <1> to <10>,

[0184] The element (M) includes Ti, or includes Zr and Ta.

[0185] <12> The solid state battery according to any one of <1> to <11>,

[0186] The solid battery further includes a battery element covered by the outer packaging portion.

[0187] The battery element contains at least one solid electrolyte selected from the group consisting of a garnet-type solid electrolyte, a LISICON-type solid electrolyte, and a perovskite-type solid electrolyte.

[0188] <13> The solid state battery according to <12>,

[0189] The battery element contains a garnet-type solid electrolyte or a LISICON-type solid electrolyte.

[0190] <14> The solid state battery according to <12> or <13>,

[0191] The battery element contains a garnet-type solid electrolyte.

[0192] <15> The solid state battery according to any one of <12> to <14>,

[0193] The outer packaging portion has a layer form.

[0194] <16> The solid state battery according to any one of <12> to <15>,

[0195] The outer packaging part is in direct contact with the surface of the battery element

[0196] <17> The solid state battery according to any one of <12> to <16>,

[0197] The outer casing is an integral sintered body of the surface of the battery element and a sintered body.

[0198] <18> The solid state battery according to any one of <12> to <17>,

[0199] The battery element comprises one or more battery structural units, wherein the battery structural unit comprises a positive electrode layer and a negative electrode layer facing each other and a solid electrolyte layer arranged between the positive electrode layer and the negative electrode layer.

[0200] The solid electrolyte is contained in one or more layers selected from the group consisting of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer.

[0201] Hereinafter, the present invention will be described in more detail based on specific examples, but the present invention is not limited to the following examples at all and can be implemented with appropriate changes within the scope of the present invention.

[0202] Example

[0203] 〔Synthesis of oxide ceramics〕

[0204] Raw materials containing lithium carbonate (Li2CO3), magnesium oxide (MgO), titanium oxide (TiO2), niobium oxide (Nb2O5), zirconium oxide (ZrO2), tantalum oxide (Ta2O5) and hafnium oxide (HfO2) were weighed so that the composition of the main phase became the composition shown in the following table. Then, water was added, sealed in a polyethylene tank made of polyethylene, and rotated at 150 rpm on a tank stand for 16 hours to mix the raw materials. It should be noted that, considering the Li deficiency during sintering, 5% by mass of lithium carbonate as a Li source was added in excess relative to the target composition.

[0205] Next, the obtained slurry was dried and pre-fired at 1050° C. for 5 hours. A mixed solvent of toluene-acetone was added to the obtained pre-fired product, and the product was pulverized by a planetary ball mill for 12 hours and then dried to obtain oxide ceramics having the compositions shown in Comparative Examples 5 to 6 and Examples 1 to 26.

[0206] 〔Evaluation of moisture resistance〕

[0207] Production of sintered body

[0208] The obtained oxide ceramics were kneaded with butyral resin, alcohol and binder to produce a slurry. The slurry was formed into a sheet on a PET film using a doctor blade method to obtain a sheet. The prepared sheets were stacked to a sheet thickness of 1.5 mm and then cut into squares with a side length of 10 mm when viewed from above. In order to suppress the volatilization of Li, the stack was fully covered with the mother powder and then sintered at 400°C to remove the butyral resin, and then sintered at 1150-1300°C for 2 hours and then cooled to obtain an outer packaging ceramic single plate. By using the Archimedean method, it was confirmed that the relative density of all sintered bodies was above 95%.

[0209] Test methods

[0210] The weight of the outer package ceramic single plate (sintered body) was measured.

[0211] After the sintered body was kept at 125°C / relative humidity 85% for 96 hours by the pressure cooker test (PCT), the weight of the sintered body was measured again. The weight change before and after the PCT was calculated and judged according to the following criteria. It should be noted that the weight change is expressed as the ratio of the weight increase to the weight before the PCT.

[0212] ◎: Weight change is less than 1% (lower limit of measurement) (optimal);

[0213] ○: Weight change is 1% or more and less than 5% (excellent);

[0214] △: Weight change is 5% or more and less than 10% (qualified: no practical problem);

[0215] ×: Weight change was 10% or more, or powdering occurred (failure: practically problematic).

[0216] (Evaluation of Reaction Resistance with Solid Electrolyte)

[0217] The oxide ceramic is mixed with the solid electrolyte, formed into a sheet, and then fired at 800°C for 5 hours. After firing, the crystalline phase is analyzed by XRD measurement and judged according to the following criteria. The tablets made in each comparative example or each embodiment are crushed into powder using a mortar. The obtained powder is put into a sample bag, and CuKα rays are used. The scanning speed is: 4.0° / min, and the measurement angle range is: XRD measurement is performed under the conditions of 10°~60° to evaluate the crystalline phase contained in the tablet. The solid electrolyte used in Comparative Examples 1 to 6 and Examples 1 to 19 is Li 6.6 Ln3Z 1.6 Ta 0.4 O 12The solid electrolytes used in Examples 20 to 26 are the garnet-type solid electrolytes, LISICON-type solid electrolytes, and perovskite-type solid electrolytes shown in Table 7.

[0218] ○: “No decomposition” of solid electrolyte and oxide ceramic (excellent);

[0219] △: "Partial decomposition" of solid electrolyte or oxide ceramic (pass: residue of crystalline phase) (no practical problem);

[0220] ×: “Complete decomposition” of the solid electrolyte or oxide ceramic (failure: practically problematic).

[0221] "No decomposition" means that Figure 3 As shown, in the XRD measurement after sintering, all peaks derived from the oxide ceramic and the solid electrolyte before sintering were clearly observed, and the side reaction between the two did not proceed. Figure 3 The XRD measurement result data when the reactivity resistance was determined in Example 4 are shown.

[0222] “Partial decomposition” means that, in XRD measurement after sintering, although all peaks derived from the oxide ceramic and the solid electrolyte before sintering are observed, a third phase or a different phase is partially generated.

[0223] “Complete decomposition” means that in XRD measurement after sintering, no peak of a compound derived from at least one of the peaks of the oxide ceramic and the solid electrolyte before sintering is observed.

[0224] The synthesis method of the solid electrolyte used for the evaluation of the reactivity resistance is as follows.

[0225] 〔Synthesis of garnet-type solid electrolyte〕

[0226] Raw materials containing lithium hydroxide monohydrate (LiOH·H2O), gallium oxide (Ga2O3), aluminum oxide (Al2O3), lanthanum hydroxide (La(OH)3), zirconium oxide (ZrO2), niobium oxide (Nb2O5), tantalum oxide (Ta2O5), and bismuth oxide (Bi2O3) are weighed so that the composition of the solid electrolyte becomes a specified composition. Next, water is added, and the mixture is sealed in a polyethylene tank made of polyethylene, and the mixture is rotated at 150 rpm on a tank stand for 16 hours to mix the raw materials. It should be noted that, in addition, in consideration of Li deficiency during sintering, 3% by mass of lithium hydroxide monohydrate (LiOH·H2O) as a Li source is added in excess relative to the target composition.

[0227] Next, the obtained slurry was dried and then pre-fired at 1000° C. for 5 hours to obtain a solid electrolyte powder having a predetermined composition.

[0228] 〔Synthesis of LISICON-type solid electrolyte〕

[0229] The raw materials containing lithium hydroxide monohydrate (LiOH·H2O), lithium phosphate (Li3PO4), vanadium oxide (V2O5), and silicon oxide (SiO2) are weighed so that the composition of the solid electrolyte becomes the specified composition. Then, water is added, and the mixture is sealed in a polyethylene tank made of polyethylene, and the mixture is rotated at 150 rpm on a tank stand for 16 hours to mix the raw materials. It should be noted that, in addition, in consideration of Li deficiency during sintering, 3% by mass of lithium hydroxide monohydrate (LiOH·H2O) as a Li source is added in excess relative to the target composition.

[0230] Next, the obtained slurry was dried and then pre-fired at 900° C. for 5 hours to obtain a solid electrolyte powder having a predetermined composition.

[0231] 〔Synthesis of perovskite-type solid electrolyte〕

[0232] Raw materials containing lithium hydroxide monohydrate (LiOH·H2O), titanium oxide (TiO2), and lanthanum hydroxide (La(OH)3) were weighed so that the composition of the solid electrolyte became a specified composition. Next, water was added, and the mixture was sealed in a polyethylene tank made of polyethylene, and the mixture was rotated at 150 rpm on a tank stand for 16 hours to mix the raw materials. It should be noted that, in addition, in consideration of Li deficiency during sintering, 3% by mass of lithium hydroxide monohydrate (LiOH·H2O) as a Li source was added in excess relative to the target composition.

[0233] Next, the obtained slurry was dried and then pre-fired at 1000° C. for 5 hours to obtain a solid electrolyte powder having a predetermined composition.

[0234] [Table 4]

[0235]

[0236] (1) Resistance to reaction with Garent-type solid electrolyte. The chemical composition mainly indicates the final composition.

[0237] As shown in Comparative Examples 1, 2, and 4, glass materials, Al2O3, and TiO2 have moisture resistance, but have low reactivity resistance with solid electrolytes and cannot be used as outer packaging materials.

[0238] Comparative Examples 3 to 6 show that the oxide ceramics containing one or two elements selected from Li, Mg, and M (eg, Ti) used in the present invention have problems in either moisture resistance or resistance to reaction with a solid electrolyte.

[0239] As shown in Examples 1 to 6, it is found that the oxide ceramic contains Li, Mg, and M (for example, Ti), so that both the reactivity resistance with the solid electrolyte and the moisture resistance can be achieved.

[0240] [Table 5]

[0241]

[0242] (1) Resistance to reactivity with Garent-type solid electrolytes

[0243] From the results of Examples 1 to 14, it can be seen that by satisfying the range of 0<Li / M≤5, 0.1≤Mg / M≤9.8, it is possible to take into account both moisture resistance and reactivity resistance with solid electrolytes. Among them, from the viewpoint of further improving the reactivity resistance with solid electrolytes, it is preferred that the oxide ceramic adopts a rock salt structure or a layered rock salt structure. In addition, from the viewpoint of moisture resistance, it is preferred that the oxide ceramic has a rock salt structure and / or a spinel structure, and more preferably has a rock salt structure.

[0244] [Table 6]

[0245]

[0246] (1) Resistance to reactivity with Garent-type solid electrolytes

[0247] The results of Examples 15 to 19 show that by satisfying the ranges of 0<Li / M≤5 and 0.1≤Mg / M≤9.8, even if M is composed of Group 4 and Group 5 elements other than Ti, both moisture resistance and resistance to reaction with the solid electrolyte can be achieved.

[0248] In addition, by comparing Examples 1 to 5, 7, 9 to 12, and 15 to 19 with Examples 6, 8, and 13 to 14, it can be seen that if the following conditions A1 to A3 are met, the moisture resistance and the reactivity resistance of the solid electrolyte are further improved, and the judgment of any characteristic is "○" or more:

[0249] ·Condition A1: 0.8≤Li / M≤4.2;

[0250] Condition A2: 0.3≤Mg / M≤9.8;

[0251] Condition A3: The oxide ceramic has a rock salt type structure.

[0252] In addition, by comparing Examples 2 to 4 and 18 to 19 with Examples 1 and 5 to 17, it can be seen that if the following conditions B1 to B3 are met, the moisture resistance and the reactivity resistance of the solid electrolyte are further improved, and the moisture resistance is judged as "◎" and the reactivity resistance is judged as "○":

[0253] Condition B1: 0.8≤Li / M≤2.1;

[0254] Condition B2: 0.8≤Mg / M≤4.2;

[0255] Condition B3: The oxide ceramic has a rock salt type structure.

[0256] [Table 7]

[0257]

[0258] (1) Resistance to reactivity with Garent-type solid electrolytes

[0259] From Examples 20 to 26, it is understood that the oxide ceramic contained in the outer casing in the present invention does not undergo a side reaction during firing even when various solid electrolytes are used.

[0260] In Tables 4 to 7, the chemical compositions are composition formulas showing the final compositions.

[0261] Industrial Applicability

[0262] The solid battery of the present invention can be applied to various fields where batteries or power storage are assumed to be used. Although it is only an example, the solid battery of the present invention can be used in the field of electronic devices. The solid battery involved in one embodiment of the present invention can also be applied to the following fields: electrical, information and communication fields using mobile devices, etc. (for example, electrical and electronic equipment fields or mobile equipment fields including mobile phones, smart phones, smart watches, laptops, digital cameras, activity meters, ARM computers, electronic paper, wearable devices, RFID tags, card-type electronic money, smart watches and other small electronic devices); home and small industrial uses (for example, power tools, golf carts, home, nursing and industrial robots); large industrial uses (for example, forklifts, elevators, port cranes); transportation system fields (for example, hybrid vehicles, electric vehicles, buses, trams, electric bicycles, electric motorcycles and other fields); power system uses (for example, various power generation, load regulators, smart grids, general household installation type storage systems and other fields); and medical uses (medical equipment fields such as headphones and hearing aids); medical uses (dose management systems and other fields); and IoT fields; space and deep sea uses (for example, space probes, submersible research vessels and other fields).

[0263] Description of Reference Numerals

[0264] 1: Battery element; 1a: Electrode layer (positive electrode layer and negative electrode layer); 1b: Solid electrolyte layer; 1c: Insulating part; 2: Outer packaging part; 2a: Main surface outer packaging part; 2b: Side outer packaging part; 3: External electrodes (external positive electrode and external negative electrode).

Claims

1. A solid battery having an outer packaging portion, wherein the outer packaging portion comprises an oxide ceramic, wherein the oxide ceramic comprises: Lithium Li; Magnesium Mg; and One or more elements M selected from the group consisting of elements of Group 4 and Group 5.

2. The solid battery according to claim 1, wherein: The oxide ceramic has the following molar ratio, 0<Li / M≤5.

3. The solid battery according to claim 1 or 2, wherein: The oxide ceramic has the following molar ratio, 0.1≤Mg / M≤9.

8.

4. The solid battery according to any one of claims 1 to 3, wherein The oxide ceramic has the following molar ratio, 0.8≤Li / M≤4.

2.

5. The solid battery according to any one of claims 1 to 4, wherein The oxide ceramic has the following molar ratio, 0.3≤Mg / M≤9.

8.

6. The solid battery according to any one of claims 1 to 5, wherein The oxide ceramic has the following molar ratio, 0.8≤Li / M≤2.

1.

7. The solid state battery according to any one of claims 1 to 6, wherein: The oxide ceramic has the following molar ratio, 0.8≤Mg / M≤4.

2.

8. The solid battery according to any one of claims 1 to 7, wherein The oxide ceramic has a rock salt type crystal structure, a spinel type crystal structure, a layered rock salt type crystal structure or a mixed phase structure thereof.

9. The solid battery according to any one of claims 1 to 8, wherein The oxide ceramic has a rock salt type crystal structure.

10. The solid battery according to any one of claims 1 to 9, wherein The element M is at least one selected from Ti, Zr, Hf, Ta and Nb.

11. The solid battery according to any one of claims 1 to 10, wherein The element M includes Ti.

12. The solid battery according to any one of claims 1 to 11, wherein The solid battery further includes a battery element covered by the outer packaging portion. The battery element contains at least one solid electrolyte selected from the group consisting of a garnet-type solid electrolyte, a LISICON-type solid electrolyte, and a perovskite-type solid electrolyte.

13. The solid battery according to claim 12, wherein: The battery element contains a garnet-type solid electrolyte or a LISICON-type solid electrolyte.

14. The solid battery according to claim 12 or 13, wherein: The battery element contains a garnet-type solid electrolyte.

15. The solid battery according to any one of claims 12 to 14, wherein: The outer packaging portion has a layer form.

16. The solid battery according to any one of claims 12 to 15, wherein: The outer package is in direct contact with a surface of the battery element.

17. The solid battery according to any one of claims 12 to 16, wherein: The outer casing is an integral sintered body of the surface of the battery element and a sintered body.

18. The solid battery according to any one of claims 12 to 17, wherein: The battery element comprises one or more battery structural units, wherein the battery structural unit comprises a positive electrode layer and a negative electrode layer facing each other and a solid electrolyte layer arranged between the positive electrode layer and the negative electrode layer. The solid electrolyte is contained in one or more layers selected from the group consisting of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer.

Citation Information

Patent Citations

  • Secondary battery and its manufacturing method

    JP2003092092A

  • Outer packaging material for electrochemical device and electrochemical device using this

    JP2007173212A

  • All-solid battery

    WO2019167856A1

  • All-solid-state battery

    WO2019181909A1